2021
DOI: 10.1055/a-1534-2388
|View full text |Cite
|
Sign up to set email alerts
|

Transpancreatic precut papillotomy versus double-guidewire technique in difficult biliary cannulation: a systematic review and meta-analysis

Abstract: Background and study aims Approximately 11 % of biliary cannulations are considered difficult. The double guidewire (DGW-T) and transpancreatic sphincterotomy (TPS) are two useful techniques when difficult cannulation exists and the main pancreatic duct is unintentionally accessed. We carried out a systematic review and meta-analysis to evaluate the effectiveness and security of both DGW-T and TPS techniques in difficult biliary cannulation. Methods We conducted a systematic review in different datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…[38][39][40] In a meta-analysis of seven RCTs by Tse et al, 40 the PGW method was reported to increase the risk of PEP without any superiority in achieving biliary cannulation compared with other techniques. Another meta-analysis of four RCTs by Guzman-Calderon et al, 39 comparing the PGW method and TPS, showed that the PGW method had a lower success rate in biliary cannulation and a higher incidence of PEP than TPS. ed ERCP, the success rate of biliary cannulation tended to be higher in the uneven method (83.3%) than in the PGW method (59%).…”
Section: The Uneven Methodsmentioning
confidence: 99%
“…[38][39][40] In a meta-analysis of seven RCTs by Tse et al, 40 the PGW method was reported to increase the risk of PEP without any superiority in achieving biliary cannulation compared with other techniques. Another meta-analysis of four RCTs by Guzman-Calderon et al, 39 comparing the PGW method and TPS, showed that the PGW method had a lower success rate in biliary cannulation and a higher incidence of PEP than TPS. ed ERCP, the success rate of biliary cannulation tended to be higher in the uneven method (83.3%) than in the PGW method (59%).…”
Section: The Uneven Methodsmentioning
confidence: 99%